Assessing the Implementation of the Best Interests of the Child Principle in Post-Divorce Custody Determinations - Angelina Patricia Halim; Mia Hadiati (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Divorce not only terminates the marital relationship between spouses but also generates significant legal consequences for children, particularly concerning child custody and the protection of their rights. This study aims to examine the legal framework governing the protection of children’s rights in post-divorce custody determinations and to assess the implementation of the best interests of the child principle in judicial practice in Indonesia. The research employs a normative legal methodology using statutory, conceptual, and case approaches. Data were collected through a comprehensive review of relevant legislation, court decisions, and legal literature and were analyzed using qualitative legal analysis. The findings indicate that the protection of children’s rights is firmly established within the Indonesian legal system through the 1945 Constitution of the Republic of Indonesia, the Marriage Law, the Child Protection Law, and the Compilation of Islamic Law. In determining custody arrangements, judges generally prioritize the welfare, safety, and overall development of the child in accordance with the best interests of the child principle. Nevertheless, the effective implementation of this principle continues to face several challenges, including limited legal awareness among parents and weaknesses in the enforcement of judicial decisions. Strengthening legal protection mechanisms and enhancing compliance with court rulings are therefore essential to ensuring the effective protection of children’s rights following divorce.